Pregnancy Complications in Women with PCOS: A Meta-Analysis (Dhaka University Journal of Science, 2021)
Polycystic ovary syndrome (PCOS) is a hormonal disorder which affects women in their reproductive ages. There might have association between maternal and neonatal complications with PCOS. The goal of this study is to look for the association between polycystic ovary syndromes (PCOS) and obstetric complications through meta-analysis on the basis of previously published studies from 2000 to 2019. In the current endeavour 17 studies involving 1975 women with PCOS and 10812 controls were selected for pooling. During pregnancy period women who have PCOS showed a significantly higher risk of developing gestational diabetes mellitus (GDM) (RR 2.51; 95% CI: 1.71-3.65), pregnancy induced hypertension (PIH) (RR 2.76; 95% CI: 2.04-3.72), preeclampsia (RR 2.14; 95% CI: 1.34-3.40), preterm birth (RR 1.41; 95% CI: 1.08-1.85) compared to controls. Neonatal birth weight is significantly lower (SMD -0.18; 95% CI: -0.33 to -0.03) compared to controls. It is concluded that women who have PCOS have greater chance of having pregnancy complications as well as risk of neonatal complications such as having low birth weight.Dhaka Univ. J. Sci. 69(2): 82-87, 2021 (July)